Hubungan Tingkat Stres Dan Depresi Dengan Tekanan Darah Pada Guru Smpn 2 Sukaraja - Putranto, Andriena Kartika Nabilla; Zulhamidah, Yenni (Syntax Corporation, 2025)
This study aims to investigate the relationship between stress and depression levels with blood pressure among teachers at SMPN 2 Sukaraja. The research method used is an analytical observational study with a cross-sectional approach. Data were collected using the DASS-21 questionnaire to measure stress and depression levels, and blood pressure was measured using a sphygmomanometer. The results show that most respondents were aged 45-54 years, predominantly female, with over 10 years of work experience. The study found no significant relationship between stress and depression levels with blood pressure among the teachers (p > 0.05). Overall, this research provides an overview of the prevalence of stress, depression, and blood pressure among teachers, as well as the factors influencing them, with a consideration of Islamic views on mental health.